KAJIAN STRUKTUR KEPRIBADIAN FREUD DALAM KISAH 1001 MALAM: STUDI PSIKOANALISIS - Syam, Essy; Rosaliza, Mita (Jurnal Ilmu Budaya, 2020)
This writing deals with analyzing Sigmund Freud’s personality structure on Arabian nights (Seribu Satu Malam). The analysis shows that in his actions, the main character, King Shahryar, is controlled by the three components of Freud’s personality structures; Id. Ego and Superego. Id controls the king when he is pushed by his Id to marry a woman and kills that woman the following day. He does that everyday for three years. It is pushed by soul drive to get pleasure when his anger and revenge are fulfilled. So, marrying and killing those women are pushed by Id. Ego’s domination is seen when the king is eager to listen to his wife’s stories and his awareness of his power also the reality he responds in leading him to his actions. At last, Superego brings him back to his good nature when he can finally accept his wife, Shahrazad. Besides, listening to Shahrazad’s stories also triggers Superego portrayed by his giving chance for Shahrazad to tell the stories, respecting her and furthermore, the good characters’quality in Shahrazad’s stories also contribute to strengthen Superego’s domination.